The influence of adding tomato extract and acetylsalicylic acid to hypotensive therapy on the daily blood pressure profiles of patients with arterial hypertension and high cardiovascular risk - Osińska, Angelika N.; Begier-Krasińska, Beata; Rzymski, Piotr; Krasińska, Aleksandra; Tykarski, Andrzej; Krasiński, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Arterial hypertension (HT) is one of the most common diseases around the world and constitutes a significant medical, social, and economic problem. Lifestyle changes, including adequate fruit and vegetable consumption, play an important role in controlling blood pressure (BP) and other cardiovascular risk factors. Aim : To compare the influence of adding acetylsalicylic acid (ASA) or standardized tomato extract (STE) to standard hypotensive therapy on the values of arterial pressure and the daily blood pressure profiles of patients with hypertension and high cardiovascular risk. Material and methods : The study included 65 patients with arterial hypertension and high cardiovascular risk. High-risk patients with primary hypertension were randomly allocated in a blinded fashion to one of two groups (ASA or STE). In each case, two visits were made: the first – before the treatment, and the second – after 4 weeks of treatment. During each visit, the patients underwent a clinical measurement of arterial pressure and an ambulatory blood pressure measurement (ABPM). Blood platelet aggregation was assessed using the VerifyNow analyzer. Results : After 4 weeks of treatment, the blood pressure values during the day (p < 0.001), during the night (p < 0.05), and in 24-h BP profiles (p < 0.01) obtained with ABPM were significantly lower in the STE group in comparison to the ASA group. The addition of STE to standard hypotensive treatment resulted in a favorable increase in the nocturnal fall of diastolic blood pressure (DBP) (by 6.5%) and mean arterial pressure (MAP) (by 3.3%). Conclusions : The use of STE is significant in HT patients with high total cardiovascular risk; it is associated with better BP control and improvements in the daily BP profile.